PENGARUH MODEL PEMBELAJARAN KONTEKSTUAL TERHADAP HASIL BELAJAR IPA KELAS IV MI MA’HAD AL-ZAYTUN - Falah Dinova Kautsar, Alvi; Indra Setiabudi, Dede; Mardani, Dadan (Cahaya Ilmu Bangsa Institute, 2024)
Effective education requires relevant and interesting teaching models. The contextual learning model addresses this need by presenting subject matter in the context of the students' real world. This helps students understand how the knowledge they acquire can be applied in their daily lives, thus increasing their learning motivation and understanding. This study used a quantitative approach with a pre-experimental one-group pretest-posttest design, specifically a one-group pretest-posttest design. Data were collected through written tests, questionnaires, and observations on 21 fourth grade students at MI Ma'had Al-Zaytun. The results of the analysis showed that the students' pretest data had an average value (mean) of 61.43. While in the post-test data, the average value (mean) increased to 84.76. The pretest data showed that only 3 out of 21 students met the KKM. then experienced an increase during the post-test, namely 16 out of 21 students met the minimum completion criteria. Based on data from structured interviews and observations conducted before and after the application of this learning model, there was also a positive response, where students showed enthusiasm, interest, activeness and high curiosity during learning. In addition, students also seem to enjoy when this learning model is applied. Thus, it can be concluded that the contextual learning model has an influence in improving the learning outcomes of natural science of grade IV students of MI Ma'had Al-Zaytun. Key Words: learning model, learning outcomes, natural science.